2019
DOI: 10.1093/femsyr/foz020
|View full text |Cite
|
Sign up to set email alerts
|

The hypoxic transcription factor KlMga2 mediates the response to oxidative stress and influences longevity in the yeast Kluyveromyces lactis

Abstract: A network of connections among hypoxia, respiration, growth and ageing, mediated by a single protein regulating lipid homeostasis, has been established in yeast.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 60 publications
(69 reference statements)
0
7
0
Order By: Relevance
“…We have demonstrated in previous work (Santomartino et al, 2019a) that KlMga2 is involved in the response to oxidative stress and regulates chronological life span. It has been reported that light can induce ROS generation and oxidative stress in S. cerevisiae (Bodvard et al, 2017).…”
Section: Oxidative Stressmentioning
confidence: 86%
See 3 more Smart Citations
“…We have demonstrated in previous work (Santomartino et al, 2019a) that KlMga2 is involved in the response to oxidative stress and regulates chronological life span. It has been reported that light can induce ROS generation and oxidative stress in S. cerevisiae (Bodvard et al, 2017).…”
Section: Oxidative Stressmentioning
confidence: 86%
“…One of the most relevant pathway regulated by KlMga2 is the biosynthesis of FAs, and we showed here that also this pathway is influenced by light stress. The connection among light stress, membrane composition or functionality, and KlMga2 is highlighted by the fact that phenotypes of the Klmga2 strains, like growth rate, respiration rate, and mitochondrial morphology, are partially or completely suppressed either by darkness or by unsaturated FAs (Micolonghi et al, 2012;Ottaviano et al, 2015;Santomartino et al, 2019a). Finally, our findings open new perspectives on the role of light in the biology of organisms (apparently) deprived of light sensing proteins and on the role of lipids and membranes in the response to light stress.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, Kl Mga1p does not regulate KlOLE1 expression, but it induces the transcription of the fatty acid desaturase FAD2 gene, not present in S. cerevisiae (Micolonghi et al, 2012; Ottaviano et al, 2015). Recent work of Santomartino et al (2019) demonstrated the involvement of the Kl Mga2p in regulation of K. lactis ROS metabolism and longevity. In this work, we investigated the role of K. lactis UPC2 gene, the orthologue of the ScUPC2/ScECM22 genes from S. cerevisiae .…”
Section: Introductionmentioning
confidence: 99%